TYPES OF STYLISTIC MEANING - Mamarasulova Sabrina Dilshod qizi; Bozorova Dilafza Ikrom qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: In the field of linguistics, various terms are used to describe specific methods by which utterances are emphasized, making them more noticeable, impactful, and thus conveying additional information. These linguistic elements are referred to as expressive means, stylistic means, stylistic markers, stylistic devices, tropes, figures of speech, and other designations. All of these terms are used without discrimination and are contrasted with the means that we commonly refer to as neutral. Linguists commonly differentiate between ordinary semantic differences, which are substantial and referential, and stylistic differences in meaning.